The Xavante in perspective: anthropology and history in the study of indigenous populations - Dent, Rosanna (Revista Brasileira de Estudos de População, 2016)
Resenha de COIMBRA JR., C. E. A.; WELCH, J. R. (Org.). Antropologia e história Xavante em perspectiva. Rio de Janeiro: Museu do Índio/Funai, 2014. 216p.